The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1055/s-0038-1632923
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiographic arthritic changes associated with two variations of tibial plateau leveling osteotomy

Abstract: Osteoarthritis (OA) progresses in the canine cranial cruciate ligament (CCL) deficient stifle. Progression of OA is also documented in canine patients after various surgical repair techniques for this injury. We evaluated the radiographic arthritic changes in canine stifle joints that have sustained a CCL injury, and compared radiographic OA scores between Tibial Plateau Leveling Osteotomy (TPLO)surgery patients receiving a medial parapatellar exploratory arthrotomy for CCL remnant removal versus those receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 7 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…The evaluation of OA in the stifle joints with moderate OA (Group C) revealed that the OA changes were not statistically significant at each pairwise comparison over time. The results obtained in both Groups B and C agree with the inverse relationship between the preoperative OA score and the difference between pre and postoperative OA scores as reported in the literature [32,33]; however, a similar relationship it was not found in the stifles without OA in Group A. Furthermore, the group of moderate OA was composed of dogs with a longer duration of lameness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The evaluation of OA in the stifle joints with moderate OA (Group C) revealed that the OA changes were not statistically significant at each pairwise comparison over time. The results obtained in both Groups B and C agree with the inverse relationship between the preoperative OA score and the difference between pre and postoperative OA scores as reported in the literature [32,33]; however, a similar relationship it was not found in the stifles without OA in Group A. Furthermore, the group of moderate OA was composed of dogs with a longer duration of lameness.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the group of moderate OA was composed of dogs with a longer duration of lameness. It was supposed that when a ligament lesion is chronic and the OA is advanced and has most likely reached a plateau prior to surgery, the progression of the cartilage degeneration of the joint is slow and the potential advancement of the OA is minimal [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although no specific surgical procedure has been established as the gold standard in veterinary medicine, intracapsular, extracapsular, and osteotomy techniques are often used (4–9). Short- and long-term complications can occur, including the progression of osteoarthritis (6, 10–19). While these techniques are typically utilized for an unstable stifle, or a complete tear, questions still remain as to how to proceed with an early partial tear where a functional, stable stifle remains.…”
Section: Introductionmentioning
confidence: 99%
“…The scores of both the BHSII-CR and the BHSII-OQ revealed a significant improvement only in the first month after surgery; the progression toward a final good outcome was then slow and, at T3, it was not statistically significant ( Table 2). This trend could be due to the morbidity of the intracapsular procedure in which open arthrotomy and bone tunnels were carried out (18,19). This finding was also supported by the percentage of change in the BHSII which showed the main improvement in the first month (Figure 2), and by the assessment of the stiffness, function and manual examination domains which had a P > 0.05 at T1 ( Table 3).…”
Section: Discussionmentioning
confidence: 61%